Avascular necrosis in HIV patients: a case–control study. (October 2013) - Whitlock, GG; Herbert, S; Copas, A; Gilson, R; Ainsworth, JG
This study investigates the association of avascular necrosis (AVN) in human immunodeficiency virus (HIV)-positive individuals with possible risk factors, including antiretroviral therapy. Clinic records of all AVN cases diagnosed up to July 2009 in HIV-positive patients attending North Middlesex Hospital, London, UK were retrospectively reviewed. For each case, one control was randomly selected, matched for gender, age, nadir CD4 count and date of HIV diagnosis. Of 15 symptomatic AVN cases identified, eight were in women. Univariate analysis demonstrated significant associations between AVN and a history of systemic steroid use ( p  = 0.004) and cumulative exposure to protease inhibitor ( p  = 0.03). Physicians should be aware of the risk of AVN with steroid use, the importance of early diagnosis and avoidance of other risk factors in order to prevent further joint involvement if possible.